EFFECTIVENESS OF MOMETASONE FUROATE IN TREATMENT OF PALATINE TONSIL HYPERTROPHY IN CHILDREN - E.V. Nosulya; I.A. Kim ("Paediatrician" Publishers LLC, 2009)
Palatine tonsil hypertrophy is one of the most frequent cases of nasal obstruction in children. Perfection of conservative treatment of palatine tonsil hypertrophy is important direction in prophylaxis of inflammatory diseases of nasal cavity and paranasal sinuses. This article presents an experience of treatment with mometasone furoate (Nasonex) in children (n = 20) in age 6-15 years old with medium and severe nasal obstruction, caused by palatine tonsil hypertrophy. It was shown that treatment during 4 weeks, including mometasone furoate, resulted in increase of summary volumetric air flow rate, passing through the nasal cavity (from 304 ± 24 to 404 ± 22 sm3/s, p = 0.002), and decrease of summary resistance in fixed pressure point (from 0.64 ± 0.08 to 0.40 ± 0.02 Pa/sm3/s, p = 0.003). The degree of choanal obstruction was decreased at the time of study from 72% to 47%. Thus, treatment with mometasone furoate favors to reduction of volumetric size of palatine tonsil and reduction of endoscopic controlled choanal obstruction. Key words: children, palatine tonsil hypertrophy, treatment, mometasone furoate. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):95-98)